1995
DOI: 10.12968/bjtr.1995.2.5.250
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary assessment for the elderly in a day hospital: 1

Abstract: Many scales have been developed to describe the functional status of elderly people before discharge from hospital. This twopart article reports on the outcome of a multidisciplinary assessment and recording method that was developed for elderly people living in the community. In the first part of this article, the literature on elderly assessment scales is reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Some of the issues (such as perceptions about ownership of records) raised in this study have not been explored elsewhere. However, our results do support the findings of other studies which encountered similar problems in developing multidisciplinary patient record documentation [7–17] . These studies revealed an over‐reliance on oral communication, lack of health‐record ownership and a perceived poor acceptance by doctors of health‐record documentation by other healthcare practitioners.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Some of the issues (such as perceptions about ownership of records) raised in this study have not been explored elsewhere. However, our results do support the findings of other studies which encountered similar problems in developing multidisciplinary patient record documentation [7–17] . These studies revealed an over‐reliance on oral communication, lack of health‐record ownership and a perceived poor acceptance by doctors of health‐record documentation by other healthcare practitioners.…”
Section: Discussionsupporting
confidence: 87%
“…A literature review revealed that most studies of multidisciplinary hospital health‐record documentation did not report any input from pharmacists [7–15] . The two exceptions reported that pharmacists were allocated a progress note section in the revised multidisciplinary health record, or were part of a steering group reviewing multidisciplinary hospital health records [16,17] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation